“Rehabilitación del grupo electrógeno de la Universidad Técnica de Cotopaxi Extensión La Maná en el bloque A”. - Avila Zambrano, Jorge Ubercio (2022)
The present investigation was developed at Universidad Técnica de Cotopaxi in La Maná block "A", with the purpose of diagnosing the required power, through electrical consumption and maximum unit demand, through the collection of data from all electrical equipment installed in the different sectors from the ground floor to the top floor, in which the amount of total equipment was obtained and the power was obtained through the characteristic plate in various places such as doctor's office, secretary, library, offices, classrooms, laboratories, etc. The importance of the study lies in the activities carried out to determine if the inactive generator set in the UTC building still had the capacity to generate electricity to supply all sectors during a conventional power failure or outage. For the complete and functional rehabilitation of the generator set, mechanical and electronic maintenance activities and adaptation of the area where it is installed were carried out, successfully achieving its total rehabilitation.